2019
DOI: 10.1002/pds.4898
|View full text |Cite
|
Sign up to set email alerts
|

Statins for primary prevention of cardiovascular disease and the risk of acute kidney injury

Abstract: PurposeTo investigate the risk of acute kidney injury (AKI) in subjects initiating statin therapy for primary prevention of cardiovascular disease (CVD).MethodsA nationwide cohort study using French hospital discharge and claims databases was performed, studying subjects from the general population aged 40 to 75 years in 2009, with no history of CVD and no lipid‐lowering drugs during the preceding 3‐year period, followed for up to 7 years. Exposure to statins (type, dose, and time since first use) and to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Second, as in many other studies, dispensed prescriptions were used as a proxy for drug prescription [ 14 , 15 ]. Third, prescribing and reimbursement of drugs also available as OTCs appears to represent an important share of the total POP [22] , contrary to most countries with advanced economies [ 22 , 29 , 30 ]. For instance in our study, amongst the 14 most-prescribed paediatric outpatient drugs, 5 were drugs also available as OTCs (helicidin, metopimazine, phloroglucinol, racecadotril, tixocortol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, as in many other studies, dispensed prescriptions were used as a proxy for drug prescription [ 14 , 15 ]. Third, prescribing and reimbursement of drugs also available as OTCs appears to represent an important share of the total POP [22] , contrary to most countries with advanced economies [ 22 , 29 , 30 ]. For instance in our study, amongst the 14 most-prescribed paediatric outpatient drugs, 5 were drugs also available as OTCs (helicidin, metopimazine, phloroglucinol, racecadotril, tixocortol).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a national administrative database analysis and followed the RECORD-PE guidelines to report the results [27] . The French National Health Data System (Système national de données de santé [SNDS]) covers 98•8% of the French population and includes reimbursement data for ambulatory care (the health insurance claims database, or Datamart de Consommation Inter-Régime [DCIR]) for all children covered by the Universal Public Health Insurance in France [29] , [29] , [30] . Every user (or parent user for children) of the French Public Health Insurance is informed of his/her opposition right regarding the use of their data for research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…40 A French population-based study also suggested that the risk of AKI is moderately higher among men exposed to statins in primary prevention. 42 Dyslipidaemia drugs were used for 35.7% of our sub-population without differences between groups, and they did not influence the AKI IRR estimation (data not shown). Cardiac or renal aetiologies related to AKI were unlikely, as a history of heart failure and renal disease are criteria for non-inclusion in the sub-population.…”
Section: Sub-population Incidence Rates Ratiosmentioning
confidence: 79%
“…37 Our findings concur with prior studies, although such comparisons are imperfect given differing definitions of outcomes and exposure. 4,5,24,38,39 Indeed, most observational studies assessed the association between statin-use and acute kidney disease in hospital discharge records. 5 Dormuth found a 34% increase in hospitalization rate for AKI within 120 days of initiating high-versus low-potency statins only in patients without history of kidney disease.…”
Section: Discussionmentioning
confidence: 99%